QUESTIONS OF EVALUATION OF POSTNATAL GROWTH IN PRETERM CHILDREN PART 2. CATCH-UP GROWTH IN PRETERM INFANTS - A. F. Kiosov (Вопросы современной педиатрии, 2014)
The term catch-up growth is now widely used in neonatology and pediatrics to describe the growth of preterm infants. Catch-up growth — is a compensatory strengthening of the body's growth after a period of slow growth. The lower the gestational age of the premature baby, the more intense catch-up growth in the future.Catch-up growth is considered an important criterion for evaluating nursing preterm infants. Formation of catch-up growth is seen as a favorable outcome. Evaluation of catch-up growth is carried out with the use of percentiles and standard deviations (Z-score). Catch-up growth has a positive effect on neurological outcome. Catch-up growth achieved if the growth rates are between 5 and 10 percentile. The values of growth are satisfactory if they are located at the 10th percentile and above. Catch-up growth is achieved with a standard deviation greater than minus 2 (Z-score). The optimal parameters are considered indicators located within two standard deviations of the mean.Estimation of the growth should be carried out optimally weekly. Growth curves help to determine when the catch-up growth begins. After discharge from the hospital catch-up growth continues. Catch-up growth occurs within the first year of life. The critical period for catch-up growth are considered the first 6 months. Subsequently, the growth rate decreases. The growth is not sufficient, if the values are below the 3 percentile. About 50% of the causes impaired growth is due to the shortage of supply. Premature babies can have problems with food and after discharge from the hospital. The very rapid growth may lead to the development of metabolic syndrome in later life. Low birth weight is associated with increased risk of hypertension, stroke, and diabetes. Compensatory growth often occurs with excessive deposition of fat. In assessing the growth necessary to accommodate the growth of muscle mass and fat mass. Maintaining optimal growth rate is important for the prevention of metabolic syndrome. Requires a meta-analysis of all published growth curves for premature babies to determine the optimal postnatal growth.